Working Paper 10: Accountability for better healthcare provision (Basel Institute on Governance Working Papers, 2011)
Strengthening accountability in public service provision is increasingly recognized as a precondition to improve the performance of the health sector in low-income countries. However, progress in this field has been hampered to a great extent because of empirical difficulties in measuring and assessing accountability.This article provides a clear operational definition of the concept and discusses how and why accountability in public health service provision presents distinct challenges to the institutional capabilities of most developing countries. On the basis of both elements a set of guidelines to empirically assess accountability in health services is offered.